Health Literacy: Individual, Social, and System Dimensions (Turkey Health Literacy Journal, 2025)
In this review, the aim is to examine the factors influencing Health Literacy (HL) at individual, community, and system levels, as well as the interaction mechanisms among these levels, and to reveal the role of HL in health promotion, reducing health inequalities, and strengthening health systems. HL is a multidimensional concept that encompasses individuals’ abilities to access, understand, evaluate, and make decisions based on health information, and is closely linked to public health and behaviour change. At the individual level, high HL supports the adoption of preventive health behaviours and treatment adherence by enhancing self-efficacy and informed decision-making capacity. At the community level, HL improves the overall health of the population through social capital, trust, solidarity, and collective health consciousness. At the system level, organizational or institutional HL strengthens the accessibility of health services, patient–professional communication, and the inclusiveness of health policies. Digital health literacy is becoming increasingly important in reducing inequalities in access to information and preventing the effects of infodemics. In conclusion, HL is not only an individual skill but also a strategic public health tool that reduces health inequalities, strengthens community-based communication, and transforms health systems.